(untitled) (Research, Society and Development, 2022)
The present work sought to demonstrate the possibility of understanding the law through literature, focusing on the process of depersonalization and censorship of the rights of those who live on the margins of society, using as a basis the short story “Mineirinho” by Clarice Lispector. A historical synthesis of the interdisciplinary relationship between law and literature, in Brazil and in the world, was elaborated, approaching its emergence and evolution, in addition to the analysis of how, through the treated work, it is possible to point out how these characteristics are manifested in the reality of Brazilian society and demonstrate how much literature can be a reflection of the most varied societies. For that, a hypothetical-deductive methodology was used based on biographies on themes inherent to the subject and a dialectical method in approaching the differences between a being endowed with rights and a depersonalized being, whose rights were repressed, and description of the interdisciplinary relationship between law and literature. and its application in society.